Effects Of Halloysite Nanotube On The Mechanical, Thermal And Morphological Properties Of Polypropylenepolyamide Blends - Ng, Chi Loon (Universiti Sains Malaysia, 2018)
Poly(propylene)/Polyamide 6/halloysite nanotube nanocomposites were prepared using extruder followed by injection molding. PP/PA6 blend ratio was fixed at 80:20 while the halloysite nanotube (HNT) loading was ranged from 2 to 8 wt%. This study is aim to evaluate the effects of HNT on flexural and thermal properties of the PP/PA6 blends. From the 3-point bending test, it was shown that the flexural modulus and strength of PP/PA6 was increased as the increasing loading of HNT. Field emission scanning electron microscopy (FESEM) results demonstrated that the droplet size of PA6 (minor phase) reduced after incorporation of HNT, which indicates the possible compatibilization effects of HNT in the PP/PA6 blends. Thermogravimetric analysis (TGA) results showed that the thermal decomposition of PP/PA6 is influenced by the loading of HNT. For the study of kinetics of thermal decomposition, Kissinger-Akahira-Sunose (KAS) model was applied. It was found that the activation energy of thermal decomposition (Ea) of the PP/PA6/HNT nanocomposites is lower than that of unfilled PP/PA6. Differential Scanning Calorimetry (DSC) results showed that the crystallinity of PP and PA6 was increased in the presence of HNT, which evidenced the nucleating effects of the HNT for the PP/PA6 blends.